Time Resolved TDLAS Investigation of Pre-ionization Effect in Dual HiPIMS Discharges - Tan, Nguyen Van; Tung, Do Hoang; Hipler, Rainer (Communications in Physics, 2014)
Time-resolved measurements have been performed during dual High Power Impulse Magnetron Sputtering (dual-HiPIMS) with two cathodes in a closed magnetic field configuration. The dual-HiPIMS system, operated at a repetition frequency f = 100 Hz and duty cycle of 1%, was equipped with two different metallic targets (Ti, Cu). Pre-ionization effect of the Ti pulse on the Cu pulse was investigated through argon excited atom density and temperature by means of tunable diode laser absorption spectroscopy. We observed an enhancement of metastable density due to pre-ionization effect. It is shown that the peak density in the Cu pulse increases about 30% for the case of 15$μ $s delay then decrease as the delay was prolonged. The effect displays even stronger in the peak density in the afterglow, as well as in the atom temperature behavior. Although metastable atoms are abundantly available in post-discharge, they play minor role in the ignition of the subsequence pulse.